Interest of cytology combined with Xpert® HPV and Anyplex® II HPV28 Detection human papillomavirus (HPV) typing: differential profiles of anal and cervical HPV lesions in HIV‐infected patients on antiretroviral therapy. Issue 10 (30th July 2018) - Nassereddine, H; Charpentier, C; Bucau, M; Joly, V; Bienvenu, L; Davitian, C; Abramowitz, L; Benabderrahmane, D; Kotelevets, L; Chastre, E; Lehy, T; Walker, F
Abstract : Objectives: The aim of the study was to assess the interest to combine cytological examination and human papillomavirus (HPV) typing of anal and cervical Papanicolaou (Pap) smears of HIV‐infected patients on combination antiretroviral therapy (cART), to evaluate whether differences in prevalence exist between anal and cervical squamous intraepithelial lesions in patients with high‐risk oncogenic HPV infection. Methods: Anal and/or cervical Pap smears were obtained by anoscopy and/or colposcopy in 238 subjects recruited consecutively in 2015: anal smears were obtained from 48 male and female patients [42 men; 35 men who have sex with men (MSM)] and cervical smears from 190 female patients. Cytological Bethesda classification was coupled with HPV typing. HPV typing was performed, on the same smears, using the Xpert ® HPV Assay, which detects only high‐risk HPV (hrHPV), and the Anyplex ® II HPV28 Detection assay, which detects hrHPV and low‐risk (lr) HPV. Results: Our data showed clear‐cut differences between the anal and cervical samples. Compared with the cervical samples, the anal samples exhibited (1) more numerous cytological lesions, which were histologically proven; (2) a higher hrHPV infection prevalence; (3) a higher prevalence of multiple hrHPV coinfections whatever HPV typing kit was used; (4) a predominance of HPV16 and HPV18/45 types. Overall, there was an almost perfect agreement between the two HPV typing assays (absolute agreement = 90.3%). Conclusions: Co‐testing consisting of cytology and HPV typing is a useful screening tool in the HIV‐infected population on cART. It allows detection of prevalence differences between anal and cervical HPV‐related lesions. As recently recommended, anal examination should be regularly performed especially in HIV‐infected MSM but also in HIV‐infected women with genital hrHPV lesions.